Tennis serve biomechanics and implications for physical conditioning - Martin, C.; Touzard, P.; Fourel, L.; Fernandez-Fernandez, J. (Strength and Conditioning Journal, 2026)
The serve is a complex overhead motion that plays a key role in tennis performance but also places high mechanical demands on the player's body. This article aimed to synthesize current biomechanical evidence on the serve and translate these findings into practical implications for physical conditioning, performance enhancement, and injury prevention. The serve is described as a coordinated proximo-distal kinetic chain in which the lower limbs initiate force production, the trunk transfers and amplifies angular momentum, and the shoulder provides the largest contribution to racket-head velocity. The elbow-forearm-wrist complex contributes to fine-tuning racket speed and orientation but is particularly sensitive to overload when proximal sequencing is altered. The article also highlights the effects of fatigue on serve mechanics, neuromuscular output, and joint function, which may compromise performance and increase injury risk during prolonged match play. Based on these biomechanical insights, evidence-informed training recommendations are proposed, emphasizing whole-body strength-power development, eccentric load tolerance, multiplanar trunk training, shoulder and scapular control, and fatigue-resistant capacities within a tennis-specific framework.